Selective aromatic production from fast pyrolysis of sugarcane bagasse lignin over ZSM-5 catalyst. (November 2021) - Soongprasit, Kanit; Sricharoenchaikul, Viboon; Atong, Duangduen
Abstract: Organosolv lignin extracted from sugarcane bagasse (BG-lignin) and commercial grade lignin (Comm-OS) were use as starting materials in this study. From our previous work, aromatic furan (2, 3-dihydrobenzofurn) was mainly produced from fast pyrolysis of BG-lignin and Comm-OS at 400–600 °C while alkyl phenol and phenol are more favorable at 700 °C. However, more thermal fragmentation was simultaneously redundant which results in low aromatic selectivity. In this work, aromatic production from lignin with molecular sieve ZSM-5 catalysts was studied using Py-GCMS instrument with biomass to catalyst ratio (B:C) of 1:1, 1:5, and 1:10. Aromatic furan and monolignol (H-unit, G-unit, and S-unit) were transform to hydrocarbon species with addition of ZSM-5 catalyst according to elimination of side chain by demethoxylation, dehydroxylation, and dealkylation reactions. Maximum aromatic production was found at B:C of 1:10 for both Comm-OS and BG-lignin of 87.31% and 88.22%, respectively, while aliphatic hydrocarbon was more abundant for BG-lignin of 43.21% (1:5). Moreover, ZSM-5 exhibit instinctive performance on MAHs and PAHs production especially at B:C of 1:5 and 1:10. Nevertheless, polymerization between MAHs results in PAHs also observed for both Comm-OS and BG-lignin. From the result, transformation of aromatic furan could be limited by introduction of molecular sieve ZSM-5 which enhance the oxygen elimination from phenol derivative and favorable for aromatic and BTX production.